Integrated Analysis and Identification of mRNAs, Circular RNAs, and Long Noncoding RNAs in Immunoglobulin A Nephropathy - Lin, Hua; Tan, Qiupei; Tang, Donge; Chen, Jiejing; Xue, Wen; Zhang, Yue; Xu, Huixuan; Dai, Yong (Saudi journal of kidney diseases and transplantation, 2023)
Circular RNAs (circRNAs) and long noncoding RNAs (lncRNAs) have a role in monitoring the appearance and progression of a great many diseases. They are useful markers for the prognosis and diagnosis of some diseases. In previous studies, the expression patterns of mRNAs, circRNAs, and lncRNAs related to immunoglobulin A (IgA) nephropathy have not been sufficiently discussed. Active prevention methods and treatment for IgA nephropathy (IgAN) are still not used. Integrated analyses and identification of the circRNAs and lncRNAs in IgAN have not been executed. We carried out a deep RNA sequencing analysis between controls and subjects with IgAN. In total, 125 antisense lncRNAs were identified to be greatly differentially expressed between the control and experimental groups. In addition, 606 mRNAs and 1275 circRNAs with differential expression levels were found between the groups. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathways were used as bioinformatic methods in this study. Our study showed the expression patterns of mRNAs, circRNAs, and lncRNAs in IgAN. We revealed the key roles of circRNAs and lncRNAs in the molecular mechanism of IgAN.